COC, CPC and OTP announce significant investment in return to high-performance sport (2020)
On Monday, the Canadian Olympic Committee (COC), Canadian Paralympic Committee (CPC) and Own the Podium (OTP) announced a $5M investment in a phased return to high-performance sport.